Changes in conventional cardiovascular risk factors and the estimated 10-year risk of acute myocardial infarction or cerebral stroke in Sami and non-Sami populations in two population-based cross-sectional surveys : the SAMINOR Study - Siri, Susanna Ragnhild; Eliassen, Bent Martin; Jacobsen, Bjarne K.; Melhus, Marita; Broderstad, Ann Ragnhild; Michalsen, Vilde Lehne; Braaten, Tonje (BMJ Open, 2019)
publishedVersion